The determinant of foreign direct investment across provinces in Indonesia: the role of market size, resources, and competitiveness - Sodik, Jamzani; Sarungu, Jj.; Soesilo, Am; Siti Aisyah Tri Rahayu, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The paper aims to analyze the determinants of foreign direct investment (FDI) in Indonesia for the period of 1990-2014, before and after the implementation of the regional autonomy policy. This study used a panel data regression technique throughout 26 province analysis units. Several important factors affecting the FDI across the provinces are considered such as market size indicators (GDP and population), resource indicators (labor force and human resources), and competitiveness indicators (electricity, road length, wages, and export). The results show that only two indicators, namely resources and competitiveness, are statistically significant in influencing the FDI inflow across the provinces. The results of this study have several important implications on public policies aimed at attracting foreign direct investments to the provinces in Indonesia. The government must pay more attention to developing and improving the infrastructure, improving the quality of human resources both in formal and non-formal education through training and skills enhancement at productive age (workforce), and determining regional wage through agreement (deliberation) between the regional governments, employers and trade unions. There is also the need for regional governments to facilitate regional exports through export promotion and export training policies for regional entrepreneurs.